PENGEMBANGAN POTENSI AYAM LOKAL UNTUK MENUNJANG PENINGKATAN KESEJAHTERAAN PETANI - Achmad Gozali Nataamijaya (Badan Penelitian dan Pengembangan Pertanian, 2010)
Native chickens potential development for supporting farmers' welfare improvementIndonesian native chickens have very good potential to be developed to create a commercial strain for supporting food security and to improve farmers' welfare. So far, at least 32 ecotypes of native chickens were documented. Each of them has special characteristics, e.g. pelung, sentul, kedu, merawang, gaok, and nusa penida. Most of the local chickens were resulted from domestication of Gallus gallus since hundred years ago. The birds could be classified into several types, i.e. meat, egg layer, dual purpose, and fancy. Government attention for developing these native chickens is limited, even though native chicken keeping activity involves most of the farmers in the villages. Native chicken diseases are commonly caused by infections of viruses, bacteria, protozoa, and parasites, however native chickens have better resistance to diseases especially avian influenza ( AI ) because its body contains higher percentage of Mx+ gene compared with the imported hybrid chicken. Selection for resistance toward AI and newcastle disease should be implemented and supported with disease control program.Keywords: Native chickens, reproductive performance, crossbreeding, poultry farming, farmers' welfare